AN ANALYSIS OF ENGLISH STUDY PROGRAM SIXTH-SEMESTER STUDENTS’ TRANSLATION QUALITY IN TRANSLATING ENGLISH PHRASAL VERBS INTO INDONESIAN - Muhammad Abdi Illahi; Fakhri Ras; Hadriana Hadriana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive research aims to describe the the students’ translation quality in translating English phrasal verbs into Indonesia. The population of this research were sixth-semester students of English Study Program, Universitas Riau.The sample was selected by using total random sampling (n: 30). The data were collected by distributing a test in the form of text which consisted of thirty two phrasal verbs. The collected data were analysed by using editing, coding, and tabulating method. Based on the data analysis, it can be concluded that the students’ quality in translating English pharal verbs into Indonesian in general was good with the mean score 74,15. Specifically, the stundents’ translation quality in translating English phrasal verb into Indonesian in terms of accuracy,clarity, and naturalness were also good with various mean scores; 73.88, 73.21, and 73.18.Keywords: Quality, Translation, Phrasal Verbs